Calcineurin-Modulated Antimicrobial Peptide Expression Is Required for the Development of Helicoverpa armigera - Wei, Jizhen; Li, Linhong; Yao, Shuangyan; Yang, Shuo; Zhou, Shuai; Liu, Xiaoguang; Du, Mengfang; An, Shiheng (Frontiers in Physiology, 2019)
Helicoverpa armigera is a universal pest around the world that has been extensively used as a model organism for agricultural pests. Calcineurin (CAN) is an important Ca2+-dependent phosphatase that is participated in various biological pathways. Here, we revealed that CAN inhibition significantly arrested H. armigera larval development by reducing larvae weight, prolonging development time and reducing pupate rates. Furthermore, CAN serves as an immune activator and regulates antimicrobial peptide (cecropin D, attacin, and gloverin) expression by binding with relish transcript factor in H. armigera. This study provides a potential target to control H. armigera by using synergistic agents for pesticides or plant-mediated RNA interference technology.